DOP82 Biological Treatment Cycles in Crohn's Disease. (30th January 2023) - Noor, N; Sousa, P; Bettenworth, D; Gomollon, F; Lobaton, T; Bossuyt, P; Casanova, M J; Ding, N; Dragoni, G; Furfaro, F; van Rheenen, P; Chaparro, M; et al.
Abstract: Background: There are now a growing number of licensed biological therapies for patients with Crohn's disease (CD) but given the costs of long-term maintenance treatment, as well as some concerns about potential side effects, there has been increasing interest in elective biological treatment discontinuation in selected patients, after a period of sustained remission. Following discontinuation, in cases of relapse, limited but reassuring evidence has suggested that remission may often be regained by retreatment with the same biological agent. Therefore, a concept has emerged where cycles of biological therapy might be used. If this treatment strategy were applied in a subgroup of patients at low-risk of relapse, cycling might allow lower, overall drug exposure but still enable appropriate disease control. However, currently, there remains uncertainty about the benefit-risk balance for using cycles of biological treatment in patients with CD. Methods: An expert panel was convened by the European Crohn's and Colitis Organisation (ECCO) to review the published literature and agree a series of consensus practice positions (CPPs) on the topic of biological treatment cycles (biocycling). An open-call was announced to all ECCO members, following which 15 individuals were selected based on their expertise, and three subgroups were formed. The panel aimed to provide evidence-based guidance to support shared decision-making. Results: A total of 14 CPP consensus statements were developed following comprehensive review of the literature. The statements evaluated multiple different aspects of biological treatment discontinuation and cycling, including the risk of relapse after elective treatment discontinuation, predictors of likely relapse or remission, safety, patient preferences and pharmacoeconomic aspects. Discussion and a preliminary voting round took place, with subsequent revision of CPP statements and supporting text, followed by a further meeting with voting to agree on final statements. Conclusion: With increasing focus on patient preferences, long-term safety and costs, elective biological treatment discontinuation may be considered for some patients with CD in remission. In cases of relapse, there have been reassuring findings on subsequent retreatment with the same biological agent. However, there is a need for more data to support routine elective treatment discontinuation and cycling in CD, especially for newer biological agents. In particular, randomised, controlled trials comparing biological cycling to current maintenance therapy strategies would be highly informative. Currently, discussions about biological treatment discontinuation and cycling should be individualised, to enable shared decision-making by patients with their clinicians.